Effect of Social Distancing on Immune System in Fighting with SARS COVID-19 - Salka Akram1, Naghma Shahzadi2, Hafiz Faizan1, Saqaina Anwar1, Muhammad Asif1* (AlQalam Journal of Medical and Applied Sciences, 2020)
Recently, the world health organization, governments, and public health experts have highlighted the potential importance of social distancing because of COVD-19 that are beneficial for the host. Coronavirus is pandemic of respiratory illness that transfer from one person to another person through cough, sneezing, mouth droplets and touching. Asymptomatic, mildly symptomatic and pre-symptomatic are three types of coronavirus. It spread fast in the whole world. Although there is no vaccine is available in the market for coronavirus while strengthening the immune system also keeps the virus away from the host. Innate, adaptive and passive immunity has power to kills infected cells. It’s done by a cytokine storm of the adaptive immune system. Though health experts say that loneliness and self-isolation cause stress which ultimately sends your immune system into exploit but in pandemic days it will be beneficial.